2021
DOI: 10.3390/pharmaceutics13111779
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier Dysfunction in CNS Disorders and Putative Therapeutic Targets: An Overview

Abstract: The blood-brain barrier (BBB) is a fundamental component of the central nervous system (CNS). Its functional and structural integrity is vital to maintain the homeostasis of the brain microenvironment by controlling the passage of substances and regulating the trafficking of immune cells between the blood and the brain. The BBB is primarily composed of highly specialized microvascular endothelial cells. These cells’ special features and physiological properties are acquired and maintained through the concerted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 353 publications
(397 reference statements)
0
51
0
Order By: Relevance
“…The barrier properties of these brain endothelial cells notably depend on tight junctions (TJ) between adjacent cells: TJs are dynamic structures consisting of several transmembranes and membrane-associated cytoplasmic proteins [ 40 ]. Moreover, several studies have reported leaky BBB is associated with the loss of integrity in TJs [ 41 ]. Our analysis suggests that the immunostainings performed after glyoxal fixation can more readily allow the identification of TJ proteins ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The barrier properties of these brain endothelial cells notably depend on tight junctions (TJ) between adjacent cells: TJs are dynamic structures consisting of several transmembranes and membrane-associated cytoplasmic proteins [ 40 ]. Moreover, several studies have reported leaky BBB is associated with the loss of integrity in TJs [ 41 ]. Our analysis suggests that the immunostainings performed after glyoxal fixation can more readily allow the identification of TJ proteins ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanisms of BBB permeability have not yet been clearly elucidated, BBB dysregulation has negative effects on a number of conditions, including stroke, TBI, Alzheimer’s disease, Parkinson’s disease, multiple sclerosis and schizophrenia [ 73 , 74 ], known to be a major contributor to the pathology of CNS disorders [ 75 ]. Specifically, glutamate excitotoxicity, in which cell death occurs as a result of excessive glutamate release from neurons and glial cells, contributes to the influx of glutamate in the BBB.…”
Section: Neurological Conditions Associated With Bbb Permeability And...mentioning
confidence: 99%
“…Other neurological conditions that are caused or exacerbated by BBB disruption and glutamate excitotoxicity and have an association with depression include Parkinson’s disease [ 84 ], Huntington’s disease [ 85 ], amyotrophic lateral sclerosis [ 86 , 87 ], multiple sclerosis [ 75 , 88 ], Alzheimer’s disease [ 89 , 90 , 91 , 92 ], epilepsy [ 93 , 94 , 95 ], aging [ 77 ] and schizophrenia [ 96 , 97 ]. There are likely interpolations to be made to similar conditions for which the association between BBB or depression lacks conclusive data [ 75 ], such as in hepatic encephalopathy [ 98 ] and brain tumors [ 99 ]. The idea of glutamatergic involvement in depression present during these conditions requires additional research.…”
Section: Neurological Conditions Associated With Bbb Permeability And...mentioning
confidence: 99%
“…Reactive astrocytes and inflammatory cells are responsible for the production of VEGF, which affects BBB integrity in brain tissue surrounding the abscess (Vaquero et al, 2001). Upregulation of VEGF in reactive astrocytes leads to downregulation of claudin-5 and occludin, resulting in BBB disruption and the development of brain edema (Archie et al, 2021).…”
Section: Brain Abscessmentioning
confidence: 99%